2022
DOI: 10.31602/jt.v4i1.7353
|View full text |Cite
|
Sign up to set email alerts
|

Pendapatan Keluarga Dan Pengetahuan Ibu Tentang Gizi Dimasa Pandemi Covid-19 Di Puskesmas Sungai Tabuk 1 Kabupaten Banjar

Abstract: Nutritional problems can occur in various groups, especially at a very vulnerable age, namely the infancy and toddler period because of the high nutritional needs to support growth and development at this time. The current condition of the Covid-19 pandemic can affect these nutritional problems due to the increasingly difficult economic conditions of the community, such as a decrease in family income which has an impact on the ability to meet daily family needs, so that it has the potential to cause various pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…Higher-income families find it easier to meet their needs, while lower-income families face greater challenges in meeting their requirements. [22] These findings are consistent with numerous studies demonstrating a relationship between family monthly income and stunting [23]; [24]; [25]; [26]; [27] however, different results with research [28] where the chi-square test yielded p=0.204, indicating no relationship between family income and stunting. This disparity may be attributed to other factors influencing the absence of a relationship between family income and stunting, such as allocation of income to non-food needs.…”
Section: Resultssupporting
confidence: 89%
“…Higher-income families find it easier to meet their needs, while lower-income families face greater challenges in meeting their requirements. [22] These findings are consistent with numerous studies demonstrating a relationship between family monthly income and stunting [23]; [24]; [25]; [26]; [27] however, different results with research [28] where the chi-square test yielded p=0.204, indicating no relationship between family income and stunting. This disparity may be attributed to other factors influencing the absence of a relationship between family income and stunting, such as allocation of income to non-food needs.…”
Section: Resultssupporting
confidence: 89%
“…The results of this study are in line with the research conducted by Rachmawati et al, 2020 with the type of cross-sectional study obtained a significant correlation between parenting styles and stunting with a p-value = 0.004, the research conducted (Noorhasanah, 2021) found a correlation between stunting and maternal parenting with a pvalue of 0.01. According to Budhathoki, 2020 this research method used datasets from the 2001, 2006, 2011 and 2016 Nepal Demographic Health Survey to describe trends in stunting in children under 5 years.…”
Section: Discussionsupporting
confidence: 92%
“…Based on research conducted by Rahmawati, 2020 shows that there is a significant relationship between stunting and parenting with a p value = 0.004. Research conducted by Noorhasanah, 2021, found a correlation between the occurrence of stunting and maternal parenting with a p value = 0.01. This fact provides evidence that the category of poor parenting, especially when providing nutrition, can provide care regarding how to feed, so that it will affect the child's stunting condition.…”
Section: Introductionmentioning
confidence: 96%